Corporate Governance in Latin American Firms: Contestability of Control and Firm Value. Issue 4 (October 2019) - Jara, Mauricio; López-Iturriaga, Félix; San-Martín, Pablo; Saona, Paolo
Using a sample of 595 firms listed in the capital markets of Argentina, Brazil, Chile, Colombia, Mexico, and Peru for the period of 2000–2015, we confirm prior literature by showing that when power distribution among several large shareholders ( contestability ) increases, firms' financial performance is enhanced. More interestingly, we find that these relations are even more significant in family-owned firms, emphasising the relevance of contesting control in this kind of firm. Furthermore, contestability has a greater influence in family firms that have the most concentrated ownership. We also find that the legal framework attenuates the impact of the balance of ownership. Here, contesting control acts as an internal corporate governance mechanism that provides an alternative to the external legal setting. Taken together, our results mean that in institutional settings characterised by weak investor protection and possible conflicts of interest among shareholders, oversight by multiple large, non-related shareholders (balanced ownership concentration) becomes an important governance mechanism.